Tailor-made and chemically designed synthesis of coumarin-containing benzoxazines and their reactivity study toward their thermosets - Froimowicz, Pablo (2016)
Coumarins are used as a natural renewable resource to synthesize coumarin-containing benzoxazine resins. The coumarin-containing benzoxazines are fully characterized in terms of their chemical structure by Fourier-transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. The influence of electronic effects caused by the substituents on the polymerization temperature is also evaluated. Thermal properties of the resulting thermosets are characterized by differential scanning calorimetry and thermogravimetric analysis, showing good stability and char yields higher than 50%. The coumarin-containing polybenzoxazine thermosets show Tg values in the range between 160 and 190 °C. Thus, the herein presented coumarin-containing benzoxazine resins are proven to be competitive monomers when compared with other petroleum-based benzoxazine resins toward the generation of high-performance thermoset.